Vojaška akademija? - Kotnik-Dvojmoč, Igor (Teorija in praksa, 1999)
In independent Slovenia, the Ministry of Defence of RS always opposed the idea of establishing classical military academy and argued for civilian form of education of commisioned officers in Slovenian army. In this light, the public announcement of initiative made by University of Maribor and MORS for establishing military academy, is of a surprise for the expert public, especially because this would be a step backwards. On the general conceptual level, civilian form of educational system is, for a small country as Slovenia, with limited needs for commisioned officers, and limited cadre and material resources, undoubtedly a good and above all a rational alternative. However, as a starting contept was not further exposed to critical estimation and extention, it cannot be optimal and is not fully completed. For this reasons, the author suggests introduction of the system of sequential detachment, and in a long term a parallel general educational programme at the civilian educational institutions and military-professional and specialized education and training at military organization. This system would offer various options regarding the beginning, duration and intensity of study for commisioned officers in the military organization
Keywords: oborožene sile; Slovenian Armed Forces; Slovenska vojska; vojaške šole; častniki; Slovenija; Slovenia